Concurrent infection of monocyte-derived macrophages with porcine reproductive and respiratory syndrome virus and Haemophilus parasuis: A role of IFNα in pathogenesis of co-infections - Kavanová, Lenka; Matiašková, Katarína; Levá, Lenka; Nedbalcová, Kateřina; Matiašovic, Ján; Faldyna, Martin; Salát, Jiří (Veterinary microbiology, 2018)
Porcine reproductive and respiratory syndrome virus (PRRSV) predisposes pigs to secondary bacterial infection caused by Haemophilus parasuis. The aim of the present study was to analyse the immune response of monocyte-derived macrophages (MDMs), serving as a model of macrophages accumulating at the site of inflammation. The second part of the study was focused on the role of IFNα in the production of inflammatory cytokines in co-infected MDMs. Concurrent infection with PRRSV and H. parasuis decreased gene expression of pro-inflammatory cytokines (IL-1β, IL-8) in MDMs in comparison with MDMs infected with PRRSV or H. parasuis alone. Our data showed that MDMs express IFNα after PRRSV infection. Thereafter, we exposed cells to the experimental addition of IFNα and a subsequent infection with H. parasuis, and detected a decreased expression/production of pro-inflammatory cytokines. Thus, we assume that IFNα, produced after PRRSV infection, could affect the immune response of monocyte-derived macrophages. Down-regulation of pro-inflammatory cytokine expression in inflammatory macrophages may allow the development of secondary bacterial infections in pigs.
Keywords: hemofilové infekce; Cell Survival; IFNα; Porcine Reproductive and Respiratory Syndrome; Porcine respiratory and reproductive syndrome virus; Interferon-alpha; cytokiny; Swine Diseases; makrofágy; viabilita buněk; Co-infections; zvířata; Bronchoalveolar Lavage; Porcine reproductive and respiratory syndrome virus; Swine; virus reprodukčního a respiračního syndromu prasat; reprodukční a respirační syndrom prasat; Haemophilus Infections; Cytokines; nemoci prasat; bronchoalveolární laváž; interferon alfa; Animals; Macrophages; Haemophilus parasuis; prasata